THE IMPACT OF MONETIZATION POLICY ON COST OF GOVERNANCE AND PRODUCTIVITY IN PUBLIC SERVICE: A STUDY OF FEDERAL MINISTRY OF SCIENCE AND TECHNOLOGY, OWERRI, IMO STATE (2015-2019) - Ekemam, Hillary I.; Njoku, Benedict Nnamdi (African Journal of Social and Behavioural Sciences, 2021)
the study, among others, is to determine whether monetization policy ensures reduction in the cost of governance.; to find out the extent to which monetization policy affects the productivity of the public servants. Descriptive research design was adopted. The data was collected from both senior and junior staff of the reference organization with the total population of 126 using monetization policy appraisal questionnaire (MPA Q) structured using Likert format. Both simple percentage and chi-square statistical tools were employed to analyze the data. Abraham Maslow‟s Hierarchy of Needs Theory was used to explain the phenomenon under study. It was found, amongst others that there is no significant relationship between monetization policy and productivity of the public servants. It was recommended amongst others that the increase in monthly emoluments as a result of monetization policy should be paid wholly and regularly to assist boost the morale of public servants towards their job.